PREFERENSI KONSUMEN TRANSPORTASI ONLINE MENGGUNAKAN ANALISIS KONJOIN - FIRDAUS, AHMAD (JURNAL ILMIAH MAKSITEK, 2023)
The development of online transportation services is increasing in Indonesia along with the growing number of users of such services. This research aims to examine consumer preferences for online transportation using conjoint analysis. The population in this study is the residents of Jambi City who are users of online transportation, totaling 144 respondents. The sampling method used is accidental sampling. The results of this study indicate the importance of price as the main factor, followed by the ease of using the application and the suitability of drivers and vehicles with the data in the application